Prednisolone but not selenium and rtPA reduces edema and improves angiogenesis after burn in mice. Issue 2 (March 2016) - Goertz, O.; Over, H.; von der Lohe, L.; Lauer, H.; Ring, A.; Daigeler, A.; Lehnhardt, M.; Kolbenschlag, J.
Highlights: Recombinant tissue plasminogen activator increased the number of sticking leukocytes. Selenium: post-traumatic wound expansion and an increase of leukocytes. Prednisolone improved angiogenesis and reduced edema formation. Abstract: Objective: Despite dramatic improvements in burn care, the major part of the therapy of thermal injuries remains symptomatical in nature. A targeted approach to accelerate angiogenesis and woundhealing and reduce edema formation remains to be found. We therefore aimed to investigate the impact of anti-inflammatory, anti-coagulative and thrombolytic agents on microcirculation after thermal injuries on the mentioned parameters. Methods: Full thickness burns were inflicted on the ears of hairless mice ( n  = 48). The effects of five intraperitoneal injections of either recombinant tissue plasminogen activator (rtPA), selenium, prednisolone or sodium chloride on microcirculation, edema formation, leukocytes and angiogenesis were investigated over a 13 day period using intravital fluorescent microscopy. Results: Prednisolone slightly improved angiogenesis (100.0% day 0 vs. 91.4% non-perfused area on day 1 post burn, p  < 0.05) and reduced edema formation (93.3% vs. 123.1% control on day 3, p  < 0.05). The rtPA-group showed the highest number of sticking leukocytes up to day 7 post burn (233%, 265%, 254% on days 1, 3, and 7, p  < 0.05 compared to baseline). A post-traumatic expansion of the non perfused area could only be observed in the selenium group (100.0% day 0, 103.1% day 1 post burn). In addition, selenium caused an increase of rolling leukocytes over the complete observation time. Conclusion: The often described positive influences of selenium for the treatment of burn patients could not be confirmed, on the contrary we found a post-traumatic expansion of the non perfused area and an increase of leukocytes in this group. The expectations to rtPA did not fulfill. Prednisolone improved angiogenesis and reduced the edema formation, both Parameters are essential for wound healing and survival of burned patients.